“Fugitive Slave / Fugitive Sailor”: Sailors’ Wardship and the Rhetoric of Emancipation in United States Maritime Reform, 1895-1898 - Thayer, Johnathan (The Northern Mariner / Le marin du nord, 2025)
In 1897, the United States Supreme Court ruled against four white merchant seamen protesting their arrest for desertion from the barque Arago in Astoria, Oregon, providing belated definition to the Thirteenth Amendment’s clause abolishing involuntary servitude. The Supreme Court’s ruling against the Arago sailors represented a nadir in the devolution of Reconstruction-era conceptions of free labor into an increasingly draconian system that insisted on absolute freedom of contract up to the point of self-enslavement. Competing conceptions of paternalism and sailors’ wardship motivated the cooptation of the rhetoric of emancipation by maritime reformers with the aim of affirming sailors’ rights to the full protections of the Thirteenth Amendment, and by extension United States citizenship.